The Formation of the Goldfish-Like Fish Derived From Hybridization of Female Koi Carp × Male Blunt Snout Bream - Wang, Yude; Yang, Conghui; Luo, Kaikun; Zhang, Minghe; Qin, Qinbo; Huo, Yangyang; Song, Jia; Tao, Min; Zhang, Chun; Liu, Shaojun (Frontiers in Genetics, 2018)
Goldfish (Carassius auratus var., GF; 2n = 100) is the most popular ornamental fish in the world. It is assumed that GF evolved from red crucian carp (C. auratus red var., RCC; 2n = 100). However, this hypothesis lacks direct evidence. Furthermore, our knowledge of the role of hybridization in the formation of new species is sparse. In this study, goldfish-like fish with twin tails (GF-L; 2n = 100) was produced by self-mating red crucian carp-like fish (RCC-L; 2n = 100) derived from the distant crossing of koi carp (Cyprinus carpio haematopterus, KOC; 2n = 100; ♀) with blunt snout bream (Megalobrama amblycephala, BSB; 2n = 48; ♂). The phenotypes and genotypes of GF-L and RCC-L were very similar to those of GF and RCC, respectively. Microsatellite DNA and 5S rDNA analyses revealed that GF-L and RCC-L were closely related to GF and RCC, respectively. The presence of a twin tail of GF-L was related to a base mutation in chordinA from G in RCC-L to T in GF-L, indicating that the lineage of RCC-L and GF-L can be used to study gene variation and function. The sequences of 5S rDNA in GF-L and RCC-L were mapped to the genomes of CC and BSB, which revealed that the average similarities of both GF-L and RCC-L to CC were obviously higher than those to BSB, supporting that the genomes of both RCC-L and GF-L were mainly inherited from KOC. GF-L and RCC-L were homodiploids that were mainly derived from the genome of KOC with some DNA fragments from BSB. The reproductive traits of GF-L and RCC-L were quite different from those of their parents, but were the same as those of GF and RCC. RCC-L easily diversified into GF-L, suggesting that RCC and GF evolved within the same period in their evolutionary pathway. This study provided direct evidence of the KOC–RCC–GF evolutionary pathway that was triggered by distant hybridization, which had important significance in evolutionary biology and genetic breeding.